1981
DOI: 10.1007/bf00002786
|View full text |Cite
|
Sign up to set email alerts
|

The lack of changes in nocturnal estuarine fish assemblages between new and full moon phases in Serpentine Creek, Queensland

Abstract: SynopsisA series of 10 sites were sampled at new and full moon phases in a vertically homogenous estuary, Serpentine Creek, Queensland, Australia. Forty-five species (14,518 individuals) were caught and analysed using standardized Shannon & Gleason diversity indices, and total number of species and individuals. The coefficients of variation for these values were greater for times than for sites. There were no significant differences between 14 pairs of new and full moon phases for R,, SE, G,, and pt, or betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
(24 reference statements)
0
10
1
Order By: Relevance
“…Cain & Dean 1976;Livingston 1976;Quinn & Kojis 1981;Bell et al 1984). Wide fluctuations in diversity values were observed between successive samples taken on differing lunar and diel phases.…”
Section: Reptantia Other Crustaceamentioning
confidence: 92%
“…Cain & Dean 1976;Livingston 1976;Quinn & Kojis 1981;Bell et al 1984). Wide fluctuations in diversity values were observed between successive samples taken on differing lunar and diel phases.…”
Section: Reptantia Other Crustaceamentioning
confidence: 92%
“…in a north Brazilian mangrove creek. Likewise, Quinn and Kojis (1981), Rooker and Dennis (1991) and Krumme et al (2004) found no differences in fish abundance between moon phases. As the factor moon phase can only be sampled once every month, it is difficult to collect a sufficiently high number of temporal replicates within a short time period to avoid mixing of monthly variations with variations related to the moon phase.…”
Section: Introductionmentioning
confidence: 90%
“…In clear-water mangroves of Madagascar and Puerto Rico, lunar periodicity had only moderate or no obvious effects on fish assemblages, respectively (Laroche et al 1997;Rooker and Dennis 1991). In turbid estuarine mangrove creeks, only minor (North Australia: Davis 1988) or no lunar cycle-related effects were found (Papua New Guinea: Quinn andKoijs 1981, North Brazil: Krumme et al 2004). Untangling the effect of lunar cycles is a formidable task due to statistical considerations (deBruyn and Meeuwig 2001) as the need to sample several lunar cycles automatically adds the effects of month and/or season (Krumme 2009).…”
Section: Introductionmentioning
confidence: 93%